Development of a Word Quest Big Book Based on the Picture and Picture Model to Significantly Improve Narrative Writing Skills - Candrian Prima Mulia; Panca Dewi Purwati (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study was motivated by the low writing skills of first-grade students at SDN 1 Gunungwuled Purbalingga. The purpose of this study was to describe the design, feasibility test, and effectiveness test of teaching materials in improving the simple text writing skills of first-grade elementary school students. The method used was Research and Development (R&D) with the ADDIE model, through observation, interviews, documentation, questionnaires, and psychomotor assessment in small-scale (n=9) and large-scale (n=22) tests. The validation results showed high feasibility, with media expert and material percentages of 91% and 93%, respectively. The average pretest and posttest scores increased from 67.05 to 90.32, with a Paired Samples t-value of 0.000 (< 0.05) and an N-Gain score of 0.75, indicating high effectiveness. Thus, the Word Quest Book is deemed very feasible and effective as teaching material for first-grade students to write simple narrative texts. The development of the Word Quest Book theoretically increases learning enthusiasm, practically serves as an innovative alternative for teachers in combining text with image media, and demonstrates that teaching materials rich in visual stimuli and contextual elements can accelerate early grade students' independent composition of simple sentences.